Depth-sensing thermal stability of accumulative fold-forged nanostructured materials. (April 2021) - Khodabakhshi, F.; Gerlich, A.P.; Verma, D.; Nosko, M.; Haghshenas, M.
Abstract: Accumulative fold-forging (AFF) as a newly developed severe plastic deformation (SPD) process based on the repetitive fold-forging steps is implemented for the production of the layered UFG ( 200 nm) AA8006 alloy and AA8006-B4 C nanocomposite ( 35 nm, 10 vol %) materials from the initial AA8006 alloy foil. The remarkably refined grains and nanoparticles can control metallic materials' mechanical properties, including the strength, strain rate dependency, and thermal stability behavior. In this context, nano-grains' local mechanical response during nanoindentation can vary considerably depending on the testing temperature, and this has yet to be discussed. In this research, after materials characterization of produced nanostructured materials according to the AFF route, the relating depth-sensing thermal stability of them assessed by conducting the nanoindentation testing at different temperatures in the range of 300–523 K. Depth sensing softening behavior is elaborated to identify the low-temperature thermal stability of processed materials. The results enunciated the occurrence of thermal softening by refining the grain structure. However, introducing the reinforcing nanoparticles lead to a pinning action that stabilized the grain boundaries. Graphical abstract: Unlabelled Image Highlights: The UFG alloy and NS nanocomposite were produced by the new AFF route. Formation of nano-grains and nanoparticles dispersion studied. Depth-sensing thermal property interrogated the more stability of nanocomposite. The importance of nanoparticles is retarding the coalescence of nano-grains.